2015
DOI: 10.1002/mbo3.240
|View full text |Cite
|
Sign up to set email alerts
|

Functional chimeras of flagellar stator proteins between E. coli MotB and Vibrio PomB at the periplasmic region in Vibrio or E. coli

Abstract: The bacterial flagellar motor has a stator and a rotor. The stator is composed of two membrane proteins, MotA and MotB in Escherichia coli and PomA and PomB in Vibrio alginolyticus. The Vibrio motor has a unique structure, the T ring, which is composed of MotX and MotY. Based on the structural information of PomB and MotB, we constructed three chimeric proteins between PomB and MotB, named PotB91, PotB129, and PotB138, with various chimeric junctions. When those chimeric proteins were produced with PomA in a Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…MotX and MotY are also needed for MotAB function in S. oneidensis (Koerdt et al ., ). However, a recent study has shown that in a PomB/MotB (PotB) chimeric protein, replacement of the C‐terminal part of the PomB, including the plug domain, by the corresponding C‐terminal part of MotB alleviates the requirement of the T‐ring for stator function in Vibrio alginolyticus (Nishino et al ., ). To determine whether the altered activity of MotAB* is linked to a change in the relationship between the stators and these ancillary proteins, motX and motY were deleted in ΔpomAB and ΔpomAB motB* strains.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…MotX and MotY are also needed for MotAB function in S. oneidensis (Koerdt et al ., ). However, a recent study has shown that in a PomB/MotB (PotB) chimeric protein, replacement of the C‐terminal part of the PomB, including the plug domain, by the corresponding C‐terminal part of MotB alleviates the requirement of the T‐ring for stator function in Vibrio alginolyticus (Nishino et al ., ). To determine whether the altered activity of MotAB* is linked to a change in the relationship between the stators and these ancillary proteins, motX and motY were deleted in ΔpomAB and ΔpomAB motB* strains.…”
Section: Resultsmentioning
confidence: 97%
“…Notably, a mutation in the plug domain of E. coli MotB (Tyr61) resulted in an up‐motile phenotype when these variants were produced in stator‐less Vibrio (Gosink and Häse, ). Similarly, a plug‐domain mutant with an Ala57Asp substitution was found to result in a pronounced gain‐of‐function phenotype for a PotB (PomB/MotB) chimeric stator in E. coli , which contained the N‐terminal 91 amino acids of PomB, including the complete plug region (Nishino et al ., ). The properties of this mutant were not studied beyond showing that swimming speed of the suppressor mutants exceeded that of the parent strain.…”
Section: Discussionmentioning
confidence: 97%
“…For the motile WT strain, agella may play an important role in cell adhesion, and they prefer to attach to hydrophobic surfaces. 15,33 In contrast, the interaction between the cell membrane and hydrophilic nanostructures may be important in non-motile strains, and E. coli is a Gram-negative bacteria whose cell membrane is negatively charged and consequently hydrophilic as mentioned above. Among the non-motile strains, RP6894 had agella, but they could not move.…”
Section: E Coli Adhesion To the Nanostructured Surfaces Depends On Bmentioning
confidence: 99%
“…In summary, this used the E. coli N-terminal domain, the ASR for the TM and plug domains (TM: residues 28–49, plug: 52–65) and then the E. coli PGD and C-terminal domain (PGD: 196–225). MotB-ASRs were constructed by PCR amplification using the chimeric plasmid pSHU1234 ( Nishino et al, 2015 ) containing PomA and PotB (a hybrid of PomB and MotB) as the cloning vector. Thirteen forward ultramer primers were designed with ∼200 nucleotide overhangs that contained a Nde I restriction site, the predicted ancestral sequences and an annealing sequence specific to MotB on PotB in pSHU1234.…”
Section: Methodsmentioning
confidence: 99%
“…Another study has exhibited that the methionine residue (M33) at the TM region of MotS is critical for K + selectivity ( Terahara et al, 2012 ). It has also been reported that switching of ion selectivity and use of dual ion into a single stator can be introduced with mutations and hybridizations of the ion-binding transmembrane region of the B-subunit ( Terahara et al, 2008 ; Nishino et al, 2015 ). However, recently it was proposed that the MotP subunit of the MotPS complex was important for the K + selectivity of the flagellar stators of Bacillus alcalophilus and Bacillus trypoxylicola ( Naganawa and Ito, 2020 ).…”
Section: Introductionmentioning
confidence: 99%